2012
DOI: 10.1093/cid/cir971
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Transmission of Norovirus Is Mainly Caused by Symptomatic Cases

Abstract: We found that symptomatic patients and HCWs were more often involved in transmission events than asymptomatic shedders. Asymptomatic HCWs rarely contributed to transmission, despite high levels of fecal virus shedding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 33 publications
4
101
0
1
Order By: Relevance
“…Although symptomatic infection is of great concern, both for individual and public health reasons [7,8], the causes of symptomatic NoV infection are poorly understood. In part, the lack of understanding is the result of a paucity of available animal models of NoV infection, none of which fully recapitulates symptoms observed in humans (reviewed in [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Although symptomatic infection is of great concern, both for individual and public health reasons [7,8], the causes of symptomatic NoV infection are poorly understood. In part, the lack of understanding is the result of a paucity of available animal models of NoV infection, none of which fully recapitulates symptoms observed in humans (reviewed in [9]).…”
Section: Introductionmentioning
confidence: 99%
“…However, IC might have adequate sensitivity comparable to those of other methods for detecting a high viral load in the early phase of the disease, since there was no apparent NV outbreak during our study period [23]. Moreover, it is still unclear whether NA patients who are positive by RT-PCR but negative by IC have infectious potential and are clinically significant [13,31,32]. The significance of false-negative cases according to the IC kit should be evaluated in a future study.…”
Section: Discussionmentioning
confidence: 92%
“…The nosocomial transmission of NoV has prompted shedding studies among health care workers to assess the potential transmission of virus (NoV GII.4) in the hospital setting following recovery. 70 The results of the study concluded the ability of symptomatic health care workers to shed and transmit the virus. Further cohort studies are clearly needed to determine the impact of viral shedding and prevalence of antibodies on transmission and susceptibility to NoV, respectively.…”
Section: Viral Shedding Natural Infection With Nov and Seroprotectionmentioning
confidence: 94%